Methodology use by shaped in cold process for the manufacture of 304 stainless steel components. - Urriolagoitia Sosa, Guillermo; Guerrero Rivera, Mario; Romero íngeles, Beatriz; Hernández Gómez, Luis Héctor; Torres San Miguel, Christopher René; Urriolagoitia Calderón, Guillermo (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper presents results for the establishment of criteria in the design of manufacturing tools by means of cold conformation of mechanical components made of stainless steel type 304. In addition values of hardness acquired by these pieces when they are obtained by cold working are reported. The results presented correspond to the performance of the designed tools and to the manufacture of self-propelling mechanical components. The starting point for the development of this work was to apply design criteria of tools for conformation in cold steels. It is important to keep in mind, that this type of steel increases its hardness when it is worn out in cold, this impedes the manufacture of components in series.